The impact of parental perinatal depressive and anxiety symptoms on newborn low birth weight - Md Ripin, Sakinah; Md Aris, Mohd Aznan; Nasreen, Hashima E (2018)
Despite significant improvement in health status in Malaysia, the prevalence of low birth weight (LBW) infants is still remained static over the past 12 years1. There are no studies conducted in Malaysia that considered the effects of psychosocial factors such as parental depression and anxiety symptoms on LBW.